THE EFFECTIVENESS OF THE 2020 POPULATION CENSUS IN SAMARINDA CITY - Sry Reski Mulka; Thalita Rifda Khaerani; Merlisa Seltiyanti Saloko; Siti Nor Aleyda (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2023)
The problems that are of interest to the careful researchers in this paper are, the challenges faced by census workers are the level of community participation, some are lacking in providing the necessary data, the neatness in filling out documents, and the lack of outreach about the population census. The purpose of this study was to determine the effectiveness and inhibiting factors for the effectiveness of the population in 2020 in the Palaran District, Samarinda City. The research focus consists of: program success, target success, satisfaction with the program, overall goal achievement. The results of this study indicate that the effectiveness of the population in 2020 in the Palaran Subdistrict, Samarinda City is based on program success indicators, the Central Bureau of Statistics has provided facilities and infrastructure to support data collection activities for census officers to make it easier for census officers to collect data in the field. The success of the target, the initial target of the sample that must be recorded was 100%, but there was a sample error of around 5%, but 95% of the community data was found by census workers who had recorded the entire community. Satisfaction with the program, all elements are satisfied with the data on the results of the 2020 population census that have been collected by census officials. Overall goal achievement has been going well. This inhibiting factor is caused by a lack of public disclosure regarding personal data, a lack of socialization regarding the 2020 population census in several regions, changes in weather, and the COVID-19 pandemic.